Estudo do comportamento da aguardente de cana durante o envelhecimento em tonéis de bálsamo - Xavier, Francisco de Assis Bessa (1984)
Some physical and chemical attributes of sugar cane brandy produced in northeast Brazil were studied during storage for one year. The freshly distilled spicit was stored at ambient temperature in 200 liter vats made from balsamo (Myroxylon balsamum L. Harms), a regional wood from Guaramiranga, Ceará. [...]